Evaluating the Representation and Responsiveness of the United Nations Commission on the Status of Women (CSW) to Diverse Women Populations Worldwide - Rincker, Meg; Henderson, Marisa; Vidigal, Renato; Delgado, Daniel (Frontiers in Sociology, 2019)
The United Nations Commission on the Status of Women (CSW) is “the principal global intergovernmental body exclusively dedicated to the promotion of gender equality and the empowerment of women.” In this article, we use a mixed-method approach to evaluate the level of United Nations Commission on the Status of Women (CSW) representation and responsiveness to diverse women populations as reflected in (a) state delegations’ participation in formal session, (b) NGO participation and (c) NGO priorities. We find that regardless of a state’s level of human development index or permanent-five status on the Security Council, the CSW displays a high level of representation and responsiveness to diverse state delegations in terms of their speaking time in formal session. The CSW was moderately representative of women’s NGOs through regional advance consultations but the level of responsiveness to women’s NGOs was low: through costly barriers to entry to gain ECOSOC status, to parallel off-site events during formal session. Although the CSW passed important resolutions, it was moderately representative and responsive at a low level to women’s NGO priorities. This was based on our surveys of attending and non-attending women’s NGOs that showed some top priorities that the 2010 CSW did not discuss or pass resolutions such as: land rights, sex trafficking, internet access for women, and the effects of climate change on women. We contend that during 1970-1994, when World Conferences on Women occurred, parallel transnational advance consultations among women’s NGOs in tandem with CSW regional consultations created a broadening of the CSW’s agenda. The CSW rationally anticipated a broader set of priority issues for diverse women populations.